Gender-Based Pragmatic Study of Hedging Devices in Selected Political News Interview of Donald Trumph and Hillary Clinton - Nurmala Ohorella (Hasanuddin University, 2019)
This research aimed to identify the linguistic items which act as hedges in political news interviews in relation to politicians’ gender, as well as to examine the pragmatic functions of these devices. Two transcripts of political news interviews of Hillary Clinton and Donald Trumph, randomly selected from CNN official website (see Appendix), were analyzed adopting Salager-Meyer’s (1997) taxonomy. The study revealed that the frequent used of hedging devices in the two interviews are modal auxiliaries, if clause, and introductory phrase. The most frequently used hedging device subcategory are the modal auxiliary “can”, “will”, “would”, and “should”. Whilst the used introductory phrase are “l think”, “l believe”, “l guess”, “as l said”, and “my understanding is that..”. The findings suggest that these hedging devices fulfill several pragmatic functions. Hedging devices is used by the two politicians to express indirectness, politeness, lack of commitment and probability. In relation to gender, the findings also reveal that the spread of hedging of the two politicians are similar